The Impact of Rating Announcement in Indonesia Stock Market - Pratama, Anzas Rustamaji (2017)
This study analyses the impact of corporate bond rating announcement on common’s stock price in the Indonesia stock market. Rating changes assigned by Fitch, Moody’s, Standard and Poor’s and PEFINDO are analysed. On the weak-form efficient market of Indonesia stock market, rating reclassification will have an impact for stockholder if the new rating contains new information or if there is redistribution of wealth within bondholder and stockholder. This study uses single market model as return-generating process and OLS regression to estimate parameter in single market model. Rating event categorized into rating downgrade, negative watchlist, rating upgrade and positive watchlist. This study finds that rating downgrade and negative watchlist consider as a good news for stockholder. Meanwhile, rating upgrade and positive watchlist is a bad news for stockholder. This result supports the theory that rating change associated with wealth redistribution. This study also finds that rating change associated with company size and grade of investment, have different magnitude of stock reaction. Meanwhile, result from rating event based on rating agency do not have systemic pattern, which is need for further study.